127k views
2 votes
Solve the system of equations by the addition method
{ 5x-y=-3
{ 4x+3y=-48

User Umuieme
by
4.9k points

1 Answer

3 votes

Answer:

(-3,-12)

Explanation:

Multiply the first equation by three to match the second equations y-term

  • 3(5x-y=-3)
  • 4x+3y=-48

  • 15x-3y=-9
  • 4x+3y=-48

The y-terms cancel out

  • 15x=-9
  • 4x=-48

Add the x-terms with each other and the terms after the equal sign as well

  • 19x=-57

Divide -57 by 19

  • x=-3

Input your x-term (-3) into one of the two first equations and multiply

Either:

  • 5(-3)-y=-3 or
  • 4(-3)+3y=-48

  • -15-y=-3 or
  • -12+3y=-48

Simplify your terms

  • -y=12
  • 3y=-36

Divide

  • y=-12
  • y=-12
User Bijal
by
5.1k points